UMPSA collaborates to expand open access to theses and dissertations with Malaysian public universities - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
PUTRAJAYA, 13 February 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has established a collaboration on Open Access to Theses and Dissertations among Malaysian public universities. This collaboration enables all 20 public universities to implement initiatives in creating an ecosystem for sharing scholarly resources among researchers, students, and the community, ultimately enhancing Malaysia’s visibility as an internationally recognised centre of knowledge.